2018
DOI: 10.1002/da.22828
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and cigarette smoking: A systematic review

Abstract: Rates of PTSD-smoking co-occurrence remain high. Notable gains have been made in relevant epidemiological and etiological research, although more work is needed in trauma-specific subpopulations. Several promising specialized treatments for comorbid smoking-PTSD have been developed and empirically tested but require replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 115 publications
4
33
1
4
Order By: Relevance
“…As mentioned, the current study found that smoking was associated with PTSD. This finding is similar to Kearns et al's finding,28 who indicated that individuals with PTSD were approximately twice as likely to be current smokers and the study of VanderVeen et al (2012)29 found that smoking relapse was associated with occupational stress among firefighters in North America. With respect to occupational characteristics, our study showed that the duration of work was associated with PTSD, while occupational injuries were not associated with PTSD, which is inconsistent with Katsavouni et al;30 their study suggested that work-related injuries (WRIs) were associated with PTSD among Greek firefighters.…”
Section: Discussionsupporting
confidence: 86%
“…As mentioned, the current study found that smoking was associated with PTSD. This finding is similar to Kearns et al's finding,28 who indicated that individuals with PTSD were approximately twice as likely to be current smokers and the study of VanderVeen et al (2012)29 found that smoking relapse was associated with occupational stress among firefighters in North America. With respect to occupational characteristics, our study showed that the duration of work was associated with PTSD, while occupational injuries were not associated with PTSD, which is inconsistent with Katsavouni et al;30 their study suggested that work-related injuries (WRIs) were associated with PTSD among Greek firefighters.…”
Section: Discussionsupporting
confidence: 86%
“…Methodologies for such analyses have been developed (e.g., Mendelian Randomization (Emdin et al, 2017) and latent causal variable (LCV) modeling (O'Connor and Price, 2018)), and we intend to apply these techniques to the large MVP dataset to further elucidate causal risk factors for PTSD and related conditions. PTSD is frequently associated with other mental health problems such as major depressive disorder (Stander et al, 2014), nicotine (Kearns et al, 2018) and alcohol (Vujanovic et al, 2019) abuse, and suicidality (Nock et al, 2009;Ramsawh et al, 2014) and with other adverse health sequelae such as obesity (Kubzansky et al, 2014) cardiovascular disease (Koenen et al, 2016), dementia (Cohen et al, 2013), type 2 diabetes (Roberts et al, 2015) and other immune-related disorders such as rheumatoid arthritis (O'Donovan et al, 2014) and hypothyroidism (Jung et al, 2018). Our PheWAS yielded a significant association between hypothyroidism in MVP with rs542933551 (in PLEKHM1).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found a probable relationship between tobacco use and mental illness, including anxiety and depression in adults. 3 , 4 , 5 , 6 , 7 In a systematic review, Kearns et al 8 found that:…”
Section: Introductionmentioning
confidence: 99%